Decision Analysis of Advertising and Price for Bilateral Competing Supply Chain. (12th June 2013) - Zhang, Cheng-Tang; Yang, Shan-Lin
Abstract : The outcome of centralized equilibrium, prisoner's dilemma equilibrium, and decentralized equilibrium under different decision models has been provided with regards to bilateral competing supply chain system, either side of which is composed of one manufacturer and one retailer. Theoretical analysis indicates a positive correlation between price and one's own advertising investment level and a negative correlation between price and the opponent's advertising investment level. Through analysis of numerical examples, the results reveal a first mover advantage that leads to prisoner's dilemma in the system as well as the impact that price and advertising competition intensity has on the supply chain's choice of decision model.